2014
DOI: 10.1002/anie.201408707
|View full text |Cite
|
Sign up to set email alerts
|

Cell‐Derived Vesicles for Single‐Molecule Imaging of Membrane Proteins

Abstract: A new approach is presented for the application of single-molecule imaging to membrane receptors through the use of vesicles derived from cells expressing fluorescently labeled receptors. During the isolation of vesicles, receptors remain embedded in the membrane of the resultant vesicles, thus allowing these vesicles to serve as nanocontainers for single-molecule measurements. Cell-derived vesicles maintain the structural integrity of transmembrane receptors by keeping them in their physiological membrane. It… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 27 publications
0
25
0
Order By: Relevance
“…3 -Because nAChRs are pentameric, ␣4␤2 can assemble with either an (␣4) 3 (␤2) 2 or an (␣4) 2 (␤2) 3 stoichiometry. We used a technique that our laboratory recently developed to perform single molecule analysis of subunit stoichiometry by spatially isolating nAChRs embedded in cell membrane-derived vesicles (42). We generated vesicles from cells expressing ␣4-gfp and ␤2-wt subunits.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…3 -Because nAChRs are pentameric, ␣4␤2 can assemble with either an (␣4) 3 (␤2) 2 or an (␣4) 2 (␤2) 3 stoichiometry. We used a technique that our laboratory recently developed to perform single molecule analysis of subunit stoichiometry by spatially isolating nAChRs embedded in cell membrane-derived vesicles (42). We generated vesicles from cells expressing ␣4-gfp and ␤2-wt subunits.…”
Section: Resultsmentioning
confidence: 99%
“…Control experiments using monomeric receptors showed that there was a low probability of having more than one receptor per isolated vesicle. Of the vesicles generated via nitrogen cavitation, ϳ15% contain a receptor (42). Each field of view was imaged for 500 frames at a frame rate of 200 ms while undergoing continuous 488 nm excitation with an intensity of 60 watt/cm 2 .…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations